The Impact of Social Media on Political Mobilization in Nigeria: A Case Study of the Obidient Movement (American Journal of Arts and Human Science, 2024)
This study demonstrates how the social media can be used for political mobilization, using the obidient movement as a case study. The emergence of the Obidient Movement in Nigeria has been intimately associated with the way in which the development of social media platforms has revolutionised political communication. This article looks at how social media affects political mobilisation in Nigeria, with a particular emphasis on the remarkable role that technology-driven communication played in the Obidient Movement’s success. The conventional boundaries of political campaigning have been rewritten with the rise of social media, giving non-traditional influencers, grassroots activism, and digital activism a greater chance to shape political discourse and election outcomes. The study employed the Uses and Gratification theory, to deduce how citizens were mobilized via social media to join the obidient movement. To achieve this, the study relied on qualitative research method that examines and synthesizes extant literature on political mobilization and the particular relevant literature on social media and political mobilization. The outcome of the study shows that despite the proliferation of fake news and misinformation on social media, it served as a tool for political mobilization for the obidient movement, as obidients used social media to form alliances, crowdfund, mobilse political support and interact with a wider audience. By exploring the pivotal role of social media in the recent Nigerian election, this article illuminates the transformative potential of these platforms in reshaping political mobilization and generating support for previously underrepresented political forces in the nation.